Synthesis, Crystal Structure, Spectroscopic Studies, NBO, AIM and SQMFF Calculations of New Pyridazinone Derivative - El Kalai, Fouad; Karrouchi, Khalid; Baydere, Cemile; Daoui, Said; Allali, Mustapha; Dege, Necmi; Brandan, Silvia Antonia (Elsevier, 2021)
A new pyridazinone derivative, (E)-ethyl 2-(5-(4-methylbenzyl)-6-oxo-3-styrylpyridazin-1(6H)-yl)acetate (2) has been synthesized and characterized by FT-IR, H-1- and C-13-NMR, ESI-MS. The (E)-configuration was confirmed by single-crystal X-ray diffraction. Theoretical B3LYP/6-31G* calculations have evidenced two stable C1 and C2 conformers where the structure of C2 form is in agreement with the corresponding experimental one. The difference in the energy values between both forms is 33.32 kJ/mol. The higher stability of C2 against C1 could probably be attributed to most negative NPA and Mulliken charges predicted on the O4 and O44 atoms of acetate groups of C2 form, as compared with C1. The calculated harmonic vibrational frequencies for C2 are consistent with their experimental ATR spectrum in the solid phase. The complete vibrational assignment of 153 vibration modes expected for C2 were performed by using the SQMFF methodology and a set of scaled force constants were also reported. C2 has revealed a higher reactivity than (E)-N'-4-methoxybenzylidene-5-methyl-1H-pyrazole-3-carbohydrazide. The Raman spectrum of both C1 and C2 forms of (2) in gas phase by using the B3LYP/6-31G* method were also predicted. Reasonable correlations are observed between the experimental and predicted H-1 and C-13 NMR and UV-Vis spectra. The intermolecular interactions in the crystal structure were analysed using Hirshfeld surface analysis and two-dimensional fingerprint plots. (C) 2020 Elsevier B.V. All rights reserved.
Karrouchi, Khalid/0000-0002-8075-8051; Fouad, El Kalai Fouad/0000-0002-4370-4118; Baydere, Cemile/0000-0002-8526-8326; Allali, Mustapha/0000-0001-7264-8314
Keywords: Synthesis; Pyridazinone; Crystal Structure; Spectroscopic Study; NBO, AIM